다이어트 진행 중인 동료와 비교한 다이어트 경험 및 계획을 가진 여중생의 식습관, 체중조절행위, 심리적 섭식장애 위험 및 우울증상 - 정애경(Aekyung Jung); 류현숙(Hyunsuk Ryu); 송경희(Kyunghee Song); 이홍미(Hongmie Lee) (Korean journal of community nutrition, 2015)
Objectives: This study was conducted to compare dietary habits, weight control behaviors, eating disorder risk and depression among middle school girls who were at various stages of dieting. Methods: Subjects were 391 girls attending a middle school in Kyeonggido, Korea. All the information was gathered by self-administered questionnaires. Eating disorder risk and depression were assessed using EAT-26 and PHQ-9, respectively. Data were compared among 4 groups; no interest in a diet (N=112), had experienced dieting (N=86), on diet currently (N=71), and plan to diet (N=122). Results: A higher number of students currently on diet tended to be unsatisfied with their own weight (p < 0.01), overestimated their weight (p < 0.05), and weighed own body frequently (p < 0.001), compared to those with only experienced dieting in the past or those who plan to diet, despite similar weights and body mass index. The students who experienced dieting in the past or those who plan to diet appeared to have several undesirable as well as desirable dietary habits and their risk of eating disorder was significantly more prevalent compared to those without an interest in dieting (p < 0.01), although significantly less prevalent compared to those currently on a diet. Conclusions: We conclude that unnecessary dieting is common among middle school girls and providing proper education with regard to healthy weights is needed to enhance their physical as well as psychological wellbeing.